Pelatihan Master of Ceremony Dalam Bahasa Inggris bagi Para Santri Taman Pendidikan Al-Qur’an (TPQ) Nurul Yaqin Bandar Lampung - Siswoyo Siswoyo; Fatma Yuniarti (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Good preparation is essential for English event hosts to perform effectively. At a minimum, they should be able to read texts in English with confidence. Taman Pendidikan Al-Qur’an (TPA) "Nurul Yaqin" frequently organizes events to commemorate Islamic holidays. To further motivate students to engage more actively in their Qur'an studies, innovative activities are needed as part of these commemorations. Training students to become English Masters of Ceremony (MCs) can serve as a creative and motivational approach. This community service program aimed to train TPA students to host events in English. The program was conducted in-person and actively involved the students. The results showed a significant positive impact, as the students enjoyed the activity and demonstrated increased enthusiasm in participating.